USING LABVIEW FOR SIMULATE DETECTION ON MOVING PLATFORMS - Rodríguez Hernández, Seriosha (Telemática, 2020)
Acoustic detection of land vehicles, aircrafts and vessels characteristic sounds, as well as acoustic surveillance on moving platforms, has become worldwide relevant in recent past decades, particularly those linked to defense, law enforcement, and national security issues. Construction of systems for such scenarios demands simulation tools for behavior prediction taking account aspects such as: sound sources and sensors directivity, sound waves atmospheric propagation losses, and acquisition channel transfer function. This paper in concerned with a software tool development to simulate the capture of acoustic signatures from fixed positions on a moving vehicle. The detection of gunshots from a fixed position using a vehicle-mounted gunshot detection system is specifically explained. Results confirm the usability of gunshot detection and direction of arrival estimation algorithms developed for ground gunshot detection systems. The proposed software was fully developed in LabVIEW graphic programming language.